2013
DOI: 10.1159/000354486
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Colonic Tumor Growth by the Selective SGK Inhibitor EMD638683

Abstract: Background: The serum and glucocorticoid inducible kinase SGK1, which was originally cloned from mammary tumor cells, is highly expressed in some but not all tumors. SGK1 confers survival to several tumor cells. Along those lines, the number of colonic tumors following chemical carcinogenesis was decreased in SGK1 knockout mice. Recently, a highly selective SGK inhibitor (EMD638683) has been developed. The present study explored whether EMD638683 affects survival of colon carcinoma cells in vitro and impacts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 64 publications
7
52
0
Order By: Relevance
“…Moreover, EMD638683 is readily soluble in water and is the first SGK inhibitor shown to be effective in vivo (Ackermann et al 2011). A newly published study showed that EMD638683 can decrease the number of colonic tumors following chemical carcinogenesis (Towhid et al 2013). Our study adds new evidence of the effectiveness of EMD638683 in vivo.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Moreover, EMD638683 is readily soluble in water and is the first SGK inhibitor shown to be effective in vivo (Ackermann et al 2011). A newly published study showed that EMD638683 can decrease the number of colonic tumors following chemical carcinogenesis (Towhid et al 2013). Our study adds new evidence of the effectiveness of EMD638683 in vivo.…”
Section: Discussionmentioning
confidence: 60%
“…Until now, several SGK1 inhibitors have been developed, including GSK650394, LY294002, SI113, and EMD638683 (Towhid et al 2013, D'Antona et al 2015. Compared with others, EMD638683 is the most selective SGK1 inhibitor (Towhid et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We next tested whether increased weight gain and fat expansion in Akt3 -/-mice fed an HFD is SGK1 dependent. EMD638683 is a small molecule SGK1 inhibitor with good oral bioavailability that has been successfully used to treat hypertension and colonic tumors in mice (34,35). Oral administration of the EMD638683 suppressed increased weight gain in Akt3 -/-mice fed an HFD ( Figure 6A).…”
Section: Akt3mentioning
confidence: 99%